ANALISIS EFEKTIVITAS PENGOBATAN HERBAL KOMPLEMENTER TERHADAP KONDISI MUAL MUNTAH PADA KEHAMILAN - Maisya Putri Sutrisno; Maslan Pangaribuan; Farida M Simanjuntak; Feri Setiadi (STIKes Medistra Indonesia, 2026)
The review of existing research shows that using fruits and plant-based remedies as non-medical treatments can help reduce nausea and vomiting and improve anemia in pregnant women. Different methods, such as eating Ambon bananas, dates, lime with or without honey, using lemon and lemongrass for aromatherapy, drinking lemongrass beverages, consuming ginger, beetroot, moringa leaves, and mixing honey with black cumin, all have been found to help decrease how often and how badly nausea and vomiting happen, and also increase hemoglobin levels significantly (p < 0.05). The success of these treatments is because of the active ingredients they contain, such as vitamin B6, iron, folate, vitamin C, flavonoids, gingerol, essential oils, and antioxidants. These ingredients help reduce too much stomach acid, improve digestion, relieve nausea, and support the production of red blood cells. Herbal treatments are considered safer, easier to find, more affordable, and have fewer side effects. That's why they are useful in midwifery care. Using these treatments can improve midwifery care by making it more thorough and based on real evidence, while also making the experience more comfortable and safe for both the mother and the baby.